2016
DOI: 10.1111/febs.13735
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone alleviates inflammation in diabetic mice fed a high‐fat diet via inhibiting advanced glycation end‐product‐induced classical macrophage activation

Abstract: Classically activated macrophages (M1) are associated with inflammation in diabetic patients. Inflammation is a known risk factor in diabetes. The present study tested the hypothesis that pioglitazone (PIO) alleviates inflammation in diabetic mice fed a high-fat diet by inhibiting advanced glycation end-product (AGE)-induced classical macrophage activation. It was found that AGE treatment promoted the transcription of proinflammatory molecules and M1 surface markers, whereas PIO increased the expression of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Previous study has demonstrated inflammation in diabetes, which features NF-κB activation induced by AGEs18. Thus, we examined the effects of Myr on NF-κB signaling and the inflammatory cytokine, TNF-α.…”
Section: Resultsmentioning
confidence: 97%
“…Previous study has demonstrated inflammation in diabetes, which features NF-κB activation induced by AGEs18. Thus, we examined the effects of Myr on NF-κB signaling and the inflammatory cytokine, TNF-α.…”
Section: Resultsmentioning
confidence: 97%
“…Monocytes and macrophages play vital roles in the formation and progression of atherosclerosis. Increased proportions of circulating monocytes, especially the inflammatory type, might be associated with accelerated atherosclerosis in diabetes which have been documented in diabetic Akita mice [ 1 ] and in STZ-induced diabetic mice [ 2 , 3 ]. Nagareddy et al's work [ 2 ] demonstrated that high glucose drives bone marrow myelopoiesis and promotes diabetes-associated atherogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that excessive inflammatory M1 monocytes/macrophages emerge in peripheral blood of both prediabetic and diabetic patients [ 4 , 5 ]. Furthermore, our previous study also found that M1 monocytes/macrophages, the inflammatory subset, increased in circulation and atherosclerotic plaque in STZ-induced diabetic mice and were related to enhanced inflammation and accelerated atherosclerosis [ 6 ]. Thus, the increased inflammatory macrophages in diabetes contribute to persistent low grade inflammation and accelerated atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%